Vertical specialization and trade surplus in China - Wang, Wei (Chandos Asian studies series., 2013)
The traditional flow of goods from primary production through to manufacturing and consumption has expanded across international borders conterminously with globalization. Vertical specialization (VS) in processing and manufacturing in China has driven export growth. In particular, intra-industry and intra-product trade between China, the US and East Asia has increased China's trade surplus over the long term. Vertical Specialization and Trade Surplus in China aims to measure the level of VS in the Chinese manufacturing industry to provide a more accurate representation of China's trade surplus, and gives empirical analysis on provinces and products with important VS activities in order to assess China's trade value-added. Exploring the vertical division of labour, and foreign direct investment (FDI) driving China's import and export imbalance, the book is divided into eight chapters, each covering an aspect of VS in China. The first chapter outlines the aims and method of the study. Chapter two covers VS trade pattern and trade surplus. Chapter three looks at FDI and the import and export imbalance, and chapter four covers the relationship between VS and import and export of foreign invested enterprises. The fifth chapter considers the causes and prospects for growth in China-US and China-Japan trade. Chapters six and seven give an empirical analysis of VS and trade surplus, and a breakdown of VS per industry in China's provinces. Finally, chapter eight considers rebalancing imports and exports in China. Measures VS across China including the developed provinces based on the newest input-output tablePresents the main provinces and products closely related to VSGives evidence on global VS trade patterns from China's national data.